Dalechampia nivea (Euphorbiaceae), a new species from Brazil - Brigato, Luiza Oliveira; Carneiro-Torres, Daniela Santos; Cordeiro, Inês; Silva, Otávio Luis Marques Da (Phytotaxa, 2025)
We describe Dalechampia nivea, a new species from high-altitude regions (700–1,190 m) within the rainforests of the Atlantic Forest domain. This species has been recorded in the states of Bahia, Espírito Santo, and Minas Gerais in eastern Brazil. Dalechampia nivea shares morphological similarities with D. pentaphylla, including leaves with five leaflets and pistillate flower calyx with six entire sepals. However, it can be distinguished by the 3-lobed involucral bracts with entire to serrated margins, lanceolate to ovate bracteal stipules, and tomentose ovary. In contrast, D. pentaphylla has 5-partite involucral bracts with lacerate margins, broadly ovate to reniform bracteal stipules, and pilose to pubescent ovary. This article includes detailed photographs, distribution maps, comments on the habitat, and a preliminary assessment of the species’ conservation status. An identification key for the Brazilian Dalechampia vines with compound or palmatisect leaves divided into five partitions is also provided.